State of the world 2020: autocratization turns viral. Issue 6 (18th August 2021) - Hellmeier, Sebastian; Cole, Rowan; Grahn, Sandra; Kolvani, Palina; Lachapelle, Jean; Lührmann, Anna; Maerz, Seraphine F.; Pillai, Shreeya; Lindberg, Staffan I.
ABSTRACT: This article analyses the state of democracy in 2020. The world is still more democratic than it was in the 1970s and 1980s, but a trend of autocratization is ongoing and affecting 25 countries in 2020, home to 34% of the world's population. At the same time, the number of democratizing countries has dwindled by nearly half, reducing to 16 countries, home to a mere 4% of the global population. Freedom of expression, deliberation, rule of law and elections show the most substantial net declines in the last decade. A major change is that India, formerly the world's largest democracy, turned into an electoral autocracy. The V-Dem data suggests that direct effects of the Covid-19 pandemic on levels of liberal democracy were limited in 2020. Still, the longer-term consequences may be worse and must be monitored closely. Due to the pandemic and state restrictions on the freedom of assembly, mass mobilization declined to its lowest level in over a decade, yet the decline in pro-democracy protests in 2020 may well prove to be short-lived once the pandemic subdues.